ASSESSMENT OF THE TAX BURDEN REFLECTING BUDGETARY FINANCIAL SUPPORTErnazarov Nuriddin (Author)79-82 - Ernazarov Nuriddin (Ecominds Press, 2025)
The article examines the significance of the tax burden as one of the most important indicators reflecting the financial support of enterprises. It highlights not only the share of the burden relative to GDP but also the lack of an acceptable methodology for its calculation at the level of economic entities or enterprises. In this regard, particular attention is paid to the analysis of the tax burden, defining it as a universal indicator that allows comparing and identifying a stable level at enterprises across various sectors of the economy. Factors influencing the level of the tax burden are presented. It is noted that enterprises are sensitive to the tax burden and must actively seek to reduce it. Several proposals are made to define its economic threshold.
Keywords: absolute and relative tax burden, tax burden forecasting, optimization, non-tax revenue, instability, inflation, tax policy, tax regime, taxation system, value added.